Optimal utilisation of PMU measurements in power system hybrid state estimators - Dubey, Anamika; Chakrabarti, Saikat; Sharma, Ankush; Terzija, Vladimir (IET generation, transmission & distribution, 2019)
A state estimator provides power system states by minimising the difference between the available measurement set and expected measurements. This minimisation problem is solved using the weighted least squares method or conventional optimisation methods. Most of the optimisation-based conventional methods used for power system state estimation are based on derivative approaches. These traditional methods suffer from problems such as the complication in handling inequality constraints, slow convergence etc. Non-linear constrained optimisation problems can be efficiently solved by the sequential quadratic programming (SQP) algorithm. SQP can be applied to small as well as large-scale non-linear programming problems having a large number of constraints. In the proposed algorithm, hybrid measurement configuration, consisting of measurements from phasor measurement units as well as conventional measurement devices, is used and applied on IEEE 14 bus, IEEE 118 bus test system and Indian northern region power grid-246 bus system.